2021
DOI: 10.1088/1361-6595/abbbd4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide in lactate solutions irradiated by non-equilibrium atmospheric pressure plasma

Abstract: A mechanism of hydrogen peroxide (H2O2) generation in plasma-activated lactated Ringer’s solution (PAL) has been analyzed. PAL was produced by irradiating a sodium lactate solution, a class of hydroxy acid, with non-equilibrium atmospheric pressure plasma (NEAPP). The concentration of H2O2 generation was dependent on the initial lactate concentrations, which ranged from 0–28 mM. However, the generation of H2O2 was inhibited by higher lactate concentration. The formation of H2O2 is proposed by catalyzed lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…Ringer’s lactate solution contains sodium chloride, potassium chloride, calcium chloride, and L-sodium lactate, and we have previously reported that the reaction products between plasma and L-sodium lactate were anti-tumor factors in PAL 17 . We have also reported that the concentration of hydrogen peroxide in PAL depends on the concentration of L-sodium lactate in irradiated Ringer’s lactate solution 28 . L-sodium lactate is an organic chemical, and the plasma treatment of L-sodium lactate is thought to cause chemical bonds to dissociate and associate; however, it remains a big mystery what components are generated by the interactions between plasma and L-sodium lactate, and what components are responsible for the selective killing of cancer cells by PAL.…”
Section: Introductionmentioning
confidence: 69%
“…Ringer’s lactate solution contains sodium chloride, potassium chloride, calcium chloride, and L-sodium lactate, and we have previously reported that the reaction products between plasma and L-sodium lactate were anti-tumor factors in PAL 17 . We have also reported that the concentration of hydrogen peroxide in PAL depends on the concentration of L-sodium lactate in irradiated Ringer’s lactate solution 28 . L-sodium lactate is an organic chemical, and the plasma treatment of L-sodium lactate is thought to cause chemical bonds to dissociate and associate; however, it remains a big mystery what components are generated by the interactions between plasma and L-sodium lactate, and what components are responsible for the selective killing of cancer cells by PAL.…”
Section: Introductionmentioning
confidence: 69%
“…Plasma exposure decreases pH (increase of hydrogen ions) and increases H 2 O 2 , and both are dependent on the initial concentration of sodium lactate in the solution before exposure. [ 35 ] However, the H 2 O 2 concentration is reduced in plasma‐activated pyruvate and glyoxylic acid solution due to the generation of acetic acid and formic acid, respectively, as measured by 1 H‐NMR spectral analysis, suggesting that the decomposition of pyruvate and glyoxylic acid might be caused by H 2 O 2 oxidation as shown in Scheme 1 (Equations and ). CH3COCOOH+H2O2CH3COOH+H2normalO+CO2, $\,{\text{CH}}_{3}\text{COCOOH}+{{\rm{H}}}_{2}{{\rm{O}}}_{2}\to {\text{CH}}_{3}\text{COOH}+{{\rm{H}}}_{2}{\rm{O}}+{\text{CO}}_{2}\text{,}$ HOCCOOH+H2O2HCOOH+H2normalO+CO2. $\,\text{HOCCOOH}+{{\rm{H}}}_{2}{{\rm{O}}}_{2}\to \text{HCOOH}+{{\rm{H}}}_{2}{\rm{O}}+{\text{CO}}_{2}\text{.…”
Section: Discussionmentioning
confidence: 99%
“…3,5‐Dibromo‐4‐nitrosobenzene sulfonate (DBNBS, 17 mM; LABOTEC) was pipetted and mixed as a spin‐trapping agent. [ 35 ] An ESR quartz tube (Aguri) with an inner diameter of 1.1 mm was filled with 100 μL plasma‐exposed solution and ESR spectra were recorded. The time from plasma exposure to the start of ESR measurement was always 60 s.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations